Methylmercury augments Nrf2 activity by downregulation of the Src family kinase Fyn - Culbreth, Megan (Neurotoxicology, 2017)
Methylmercury (MeHg) is a potent developmental neurotoxicant that induces an oxidative stress response in the brain. It has been demonstrated that MeHg exposure increases nuclear factor erythroid 2-related factor 2 (Nrf2) activity. Nrf2 is a transcription factor that translocates to the nucleus in response to oxidative stress, and upregulates phase II detoxifying enzymes. Although, Nrf2 activity is augmented subsequent to MeHg exposure, it has yet to be established whether Nrf2 moves into the nucleus as a result. Furthermore, the potential effect MeHg might have on the non-receptor tyrosine kinase, Fyn, has not been addressed. Fyn phosphorylates Nrf2 in the nucleus, resulting in its inactivation, and consequent downregulation of the oxidative stress response. Here, we observe Nrf2 translocates to the nucleus subsequent to MeHg-induced oxidative stress. This response is concomitant with reduced Fyn expression and nuclear localization. Moreover, we detected an increase in phosphorylated Akt and glycogen synthase kinase 3 beta (GSK-3β) at activating and inhibitory sites, respectively. Akt phosphorylates and inhibits GSK-3β, which subsequently prevents Fyn phosphorylation to signal nuclear import. Our results demonstrate MeHg downregulates Fyn to maintain Nrf2 activity, and further illuminate a potential mechanism by which MeHg elicits neurotoxicity.